Flavin Oxidoreductase‐Mediated Regeneration of Nicotinamide Adenine Dinucleotide with Dioxygen and Catalytic Amount of Flavin Mononucleotide for One‐Pot Multi‐Enzymatic Preparation of Ursodeoxycholic Acid. Issue 11 (22nd March 2019) - Chen, Xi; Cui, Yunfeng; Feng, Jinhui; Wang, Yu; Liu, Xiangtao; Wu, Qiaqing; Zhu, Dunming; Ma, Yanhe
Abstract: Ursodeoxycholic acid (UDCA), a pharmaceutical ingredient widely used in clinics, can be prepared from chenodeoxycholic acid (CDCA) by the epimerization of the 7α‐OH group. In this study, a nicotinamide adenine dinucleotide (NAD + ) regeneration system was developed by using flavin oxidoreductase (FR) and flavin mononucleotide (FMN). Only catalytic amount of FMN is required for the effective NAD + recycling. FR/FMN system was then applied in the oxidation of CDCA to 7‐ketolithocholic acid (7‐keto‐LCA) by NAD + ‐dependent 7α‐hydroxysteroid dehydrogenase ( Bs ‐7α‐HSDH) from Brevundimonas sp., which showed extremely high enzyme activity toward CDCA ( k cat / K m =8050 s −1 ⋅ mM −1 ). When Escherichia coli whole cells coexpressing Bs ‐7α‐HSDH and FR genes were used as biocatalyst, CDCA (50 mM) was completely converted to 7‐keto‐LCA with the turnover number of FMN being 227 and 58.8 g ⋅ L −1 ⋅ d −1 space‐time yield of 7‐keto‐LCA. For the reduction of 7‐keto‐LCA, nicotinamide adenine dinucleotide phosphate (NADPH)‐dependent 7‐β‐hydroxysteroid dehydrogenase ( Cm ‐7β‐HSDH) from Clostridium sp. Marseille was employed with alcohol dehydrogenase from Thermoanaerobacter brockii ( Tb ADH) and iso ‐propanol as co‐factor regeneration system. When E. coli whole cells coexpressing Cm ‐7β‐HSDH and Tb ADH genes were used as biocatalyst, 40 mM 7‐keto‐LCA was reduced to UDCA with 26.8 g ⋅ L −1 ⋅ d −1 space‐time yield. The oxidation and reduction were then carried in a one‐pot concurrent mode, 12.5 mM CDCA was completely converted to UDCA. The epimerization of CDCA to UDCA proceeded to completion at the substrate concentration of 30 mM in the one‐pot sequential process. Therefore, the complete conversion of CDCA to UDCA in one‐pot has been realized by employing 7α‐HSDH and 7β‐HSDH of different co‐factor specificities with independent co‐factor recycling systems. The cholic acids, especially UDCA, exert inhibitive effect on the activities of these enzymes, preventing the complete epimerization of 7α‐OH at higher substrate loading. This inhibition issue should be solvable by engineering the involved enzymes, that is currently pursued in our laboratory. Abstract :